To rewrite the expression \( 19 - 7(2x - 3) \) using the distributive property, you can start by rewriting the subtraction as addition. This can be done by expressing the subtraction in terms of a negative:
-
Rewrite the expression using addition: \[ 19 - 7(2x - 3) = 19 + (-7)(2x - 3) \]
-
Now, apply the distributive property to the term \(-7(2x - 3)\): \[ = 19 + (-7)(2x) + (-7)(-3) \]
-
Calculate the products: \[ = 19 - 14x + 21 \]
-
Combine the constant terms \( 19 \) and \( 21 \): \[ = (19 + 21) - 14x \] \[ = 40 - 14x \]
So the equivalent expression for \( 19 - 7(2x - 3) \) is: \[ 40 - 14x \]